Structural analysis of wind blades with and without power control - Brahim Kouadria; Mohammed Debbache (International Journal of Energetica)
The blade is the principal element in the wind rotor mechanism. the efficiency of the wind turbine depends on the optimal geometry of this element, as well as its structural configuration. This work presents a contribution to wind blade structural design. the blade structure was evaluated without the control power operating case and with the power control case. In this case, an 80KW horizontal axis wind turbine design was proposed. the process begins with design and aerodynamic analysis based on blade element momentum theory by using Qblade software to determine the blade geometry. The blade structure was defined by the NuMad package, it is composed of two parts. the shell part is four layers of composite materials and the rib part has a sandwich panel shape. The evolution of structure was done by the Co-Blade package. The results show a decreasing  in displacement decreased to 64% at the tip of the blades which leads to the stress at the leading and trailing edge being negligible. That proves the importance of a control power system in the protection of the blade structure and turbine generator in the operating case under high wind velocity and ensures the stability of the power output value.